Cardiac function and tadalafil used for treating fetal growth restriction in pregnant women without cardiovascular disease. (3rd August 2019) - Tanaka, Kayo; Tanaka, Hiroaki; Maki, Shintaro; Kubo, Michiko; Nii, Masafumi; Magawa, Shoichi; Hatano, Fumi; Tsuji, Makoto; Osato, Kazuhiro; Kamimoto, Yuki; Umekawa, Takashi; Ikeda, Tomoaki
Abstract: Background: The aim of the present study was to evaluate tadalafil for the treatment of fetal growth restriction (FGR) and the cardiac function in pregnant women without cardiovascular disease who used tadalafil for this reason. Materials and methods: We examined nine pregnant women without cardiovascular disease who were using tadalafil to treat FGR. Maternal heart rate, systolic blood pressure (BP), and echocardiographic findings were assessed before and after tadalafil use. Results: Diastolic BP was lower after compared to that before using tadalafil, but the difference was not significant. Echocardiographic findings were not significantly different before and after tadalafil use. Conclusions: Tadalafil did not adversely affect pregnant women without cardiovascular disease and was considered acceptable for use since it did not affect the mother's cardiac function.